2022
DOI: 10.1002/jbio.202200187
|View full text |Cite
|
Sign up to set email alerts
|

Remote photoplethysmography with consumer smartphone reveals temporal differences between glabrous and nonglabrous skin: Pilot in vivo study

Abstract: Photoplethysmography (PPG) is a noninvasive optical technology, with applications including vital sign extraction and patient monitoring. The PPG acquisition skin type may be of importance. Skin is either nonglabrous (~90%) or glabrous (~10%). Clinical PPG collection is typically from glabrous (fingerpad), while proliferating wearables collecting PPG, which may perform critical functions like arrythmia detection, often acquire from atypical sites. Glabrous skin has significant differences from nonglabrous, inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 28 publications
1
8
0
Order By: Relevance
“…Firstly, we obtained statistically significant results to demonstrate that the PPG signal in glabrous skin is stronger than in non-glabrous skin. Prior to the current study, these results were derived on a single subject [ 19 ] or a small number of subjects [ 15 ], which did not allow any feasible extrapolation.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Firstly, we obtained statistically significant results to demonstrate that the PPG signal in glabrous skin is stronger than in non-glabrous skin. Prior to the current study, these results were derived on a single subject [ 19 ] or a small number of subjects [ 15 ], which did not allow any feasible extrapolation.…”
Section: Discussionmentioning
confidence: 99%
“…The experimental protocol was performed as in our previous study [ 15 ]. Briefly, subjects rested for 10 min in the collection area before the initiation of data collection.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Burton et al used a smartphone‐based device to measure the photo‐plethysmography (PPG) signal from the glabrous and non‐glabrous areas of the skin in the hands of five healthy volunteers [7]. In this study, it was found that by measuring the amplitude ratio and temporal lag from the two types of skin, the collected data exhibited a statistically significant lead time of the glabrous signal over the non‐glabrous (by 52 ms), and a variable yet interesting trend of an increase in amplitude of the glabrous signal over the non‐glabrous (31%, but lacking statistical significance at α = 0.05).…”
mentioning
confidence: 99%